Pengaruh Kompetensi Guru dan Metode Pembelajaran Terhadap Prestasi Belajar Siswa: (Studi Kasus di SMP Al-Hikmah Balongrejo Sumobito Jombang) - Abdul Rouf (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
This study aims to determine and analyze the Effect of Teacher Competence and Learning Methods on Student Learning Achievement at Al-Hikmah Middle School Balongrejo Sumobito Jombang. This research is a quantitative study, using data collection techniques namely observation, interviews, questionnaires and documentation. The data analysis technique uses multiple linear regression analysis techniques that are managed through SPSS version 25. From the results of the study based on multiple linear regression analysis, the results obtained that teacher competency and learning methods significantly influence student achievement. This can be seen from the results of the F test with a F value of 8.307 and a significance value below 0.05 which is 0.001a. Which means, the working hypothesis (Ha) is ACCEPTED and the null hypothesis (Ho) is REJECTED.